2017
DOI: 10.1097/md.0000000000007828
|View full text |Cite
|
Sign up to set email alerts
|

The association between peptic ulcer diseases and mental health problems

Abstract: This study aimed to investigate the association between the prevalence of peptic ulcer disease (PUD) and mental health problems, such as severe stress, depressive mood, and suicidal ideation.The population-based cross-sectional study was comprised of 14,266 subjects participating in the fourth annual Korea National Health and Nutrition Examination survey from 2007 to 2009. The participants were divided into 2 groups according to the self-reported questionnaires: the PUD group and the non-PUD group. The associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 28 publications
(31 reference statements)
6
31
0
1
Order By: Relevance
“…In addition, this study used control groups matched for demographic factors, and past medical histories were rigorously adjusted using the CCI. The previous studies also mentioned an association between depression and peptic ulcers 5,9,15 . A nationwide cohort study described that the depression patients had 1.35 times higher risk of peptic ulcer (95% CI = 1.29-1.42) 5 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In addition, this study used control groups matched for demographic factors, and past medical histories were rigorously adjusted using the CCI. The previous studies also mentioned an association between depression and peptic ulcers 5,9,15 . A nationwide cohort study described that the depression patients had 1.35 times higher risk of peptic ulcer (95% CI = 1.29-1.42) 5 .…”
Section: Discussionmentioning
confidence: 93%
“…A nationwide cohort study described that the depression patients had 1.35 times higher risk of peptic ulcer (95% CI = 1.29-1.42) 5 . Another cross-sectional study reported elevated odds of depression in peptic ulcer patients 9 . However, neither study matched the control group for the income and region of residence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, stress-induced gastric ulcers develop because of stress and its associated anxiety [46]. This mental anxiety is known to increase SNS activity, while decreasing PNS activity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we examined the effects of ASH on novel environmental stress and high-fear stress. It is known that environmental factors, such as increased fear of heights, activate the SNS and inhibit the PNS, resulting in various anxiety-related behaviors and impaired physical condition [46,48,49]. In addition, patients suffering from anxiety disorders have excessive SNS activity and PNS inactivation, and similar symptoms are observed even in rodents [31,32,33].…”
Section: Discussionmentioning
confidence: 99%